2015
DOI: 10.1111/geoj.12154
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and opportunities of social capital for adaptation to climate change: a case study on the Isles of Scilly

Abstract: Small islands are among regions most affected by the impacts of global climate change. They are regarded as particularly vulnerable, but from a different point of view, island societies also feature a particular sociocultural resilience, which distinguishes them from continental societies. How do social structures increase the adaptive capacity of small islands towards sea-level rise? I consider the concept of social capital as applicable in order to understand the role of communities and collective action in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…Such an understanding refers, on the one hand, to the geomorphological dynamics of the intertidal and coastal zone, and on the other hand to changing anthropogenic perceptions, use of, and interference with the coast, as well as the potential of community action in vulnerable areas. This and many other studies (e.g., Baldacchino, 2005;Groome Wynne, 2007;Kilpatrick & Falk, 2003;Petzold, 2016;Petzold & Ratter, 2015) showed that social capital can be an important resource for various purposes on small islands, including adaptation to climate change.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Such an understanding refers, on the one hand, to the geomorphological dynamics of the intertidal and coastal zone, and on the other hand to changing anthropogenic perceptions, use of, and interference with the coast, as well as the potential of community action in vulnerable areas. This and many other studies (e.g., Baldacchino, 2005;Groome Wynne, 2007;Kilpatrick & Falk, 2003;Petzold, 2016;Petzold & Ratter, 2015) showed that social capital can be an important resource for various purposes on small islands, including adaptation to climate change.…”
Section: Resultssupporting
confidence: 51%
“…In Flushing, this involved a semi-structured interview with a representative from the local council, non-structured interviews with local inhabitants, and several observations of erosion and post-flooding conditions of the town. For an extended analysis of the qualitative research approach in the Isles of Scilly, see Petzold (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), the experience of this one small neighbourhood in New Orleans is replicated in other places worldwide, as Petzold's example of the Isles of Scilly (2016, this volume) illustrates. It is not just the quantification of the social network or its connectivity, but rather how such networks can be mobilised to benefit the community (Petzold , 116), especially in efforts to adapt to climate change. As the article states, the relevance of social capital for adaptation to climate change is spatially variable and ‘depends on the dimension of vulnerability of the island and its institutional setting’ (p. 122).…”
Section: Confusing Vulnerability and Resiliencementioning
confidence: 99%
“…An inter-disciplinary approach adds a much-needed critical voice to integrated climate change research because of its focus on finding new methods of finding new knowledge and on applying this new knowledge to particular settings (Murphy, 2011). After all, "adaptation to climate change on small islands is not only a technical challenge, but particularly a political and social task" (Petzold, 2015).…”
Section: Climate Change and Positivist Sciencementioning
confidence: 99%